Vulvar leiomyoma mimicking Bartholin's gland cyst: A case report - Saeed Baradwan; Hassan M. Latifah; Haneen Al-Maghrabi; Abdulmonem M. Almutawa (Case Reports in Women's Health)
Vulvar leiomyomas are rare benign tumors originating from smooth muscle cells of the vulvar tissue. This report concerns a 31-year-old woman who presented with a painless vulvar mass measuring 5 × 4 cm. The mass was clinically diagnosed as a Bartholin cyst due to its non-tender and soft nature, and as a result the patient underwent wide local excision of the vulvar mass. Histopathology confirmed it to be benign vulvar leiomyoma. This case emphasizes the importance of thorough clinical evaluation and accurate histopathological examination in identifying vulvar masses. This report underscores the diagnostic difficulties associated with rare vulvar lesions and stresses the necessity of a comprehensive approach to their evaluation and treatment.